Memoria 2024 del Centro de Investigación de Agroindustria (CIA) - Instituto Nacional de Tecnología Agropecuaria (INTA). Centro de Investigación de Agroindustria (Centro de Investigación de Agroindustria (CIA), 2025)
The CIA integrates its two institutes: the Rural Engineering Institute and the Food Technology Institute, and is part of INTA's National Center for Agricultural Research (CNIA). The CIA's objectives for the 2021-2025 period are to promote added value in agri-food and agro-industrial production by boosting the competitiveness of value chains within the framework of Industry 4.0, with a Bioeconomy approach, differentiating products, improving efficiency in production processes, and reducing costs. To foster a culture of innovation within the institution that drives sustainable development, in virtuous coordination with the different actors of the pentahelix (government, universities, entrepreneurs, NGOs, and society). These activities are carried out in coordination with INTA's other regional and research centers and inter-institutionally with public and private organizations, both nationally and internationally.